Molecular Engineering of Conjugated Polymers for Solar Cells: An Updated Report. Issue 20 (30th December 2016) - Xiao, Shengqiang; Zhang, Qianqian; You, Wei
Abstract : The device efficiency of polymer:fullerene bulk heterojunction solar cells has recently surpassed 11%, as a result of synergistic efforts among chemists, physicists, and engineers. Since polymers are unequivocally the "heart" of this emerging technology, their design and synthesis have consistently played the key role in the device efficiency enhancement. In this article, the first focus is a discussion on molecular engineering (e.g., backbone, side chains, and substituents), then the discussion moves on to polymer engineering (e.g., molecular weight). Examples are primarily selected from the authors contributions; yet other significant discoveries/developments are also included to put the discussion in a broader context. Given that the synthesis, morphology, and device physics are inherently related in explaining the measured device output parameters ( Jsc, Voc and FF), we will attempt to apply an integrated and comprehensive approach (synthesis, morphology, and device physics) to elucidate the fundamental, underlying principles that govern the device characteristics, in particular, in the context of disclosing structure‐property correlations. Such correlations are crucial to the design and synthesis of next generation materials to further improve the device efficiency. Abstract : Recent progress (2012–2016) in polymer:fullerene bulk‐heterojunction solar cells is reviewed. The intrinsic complexity of such solar cells urges the community to apply an integrated and comprehensive approach – including synthesis, morphology, and device physics – to elucidate the fundamental underlying principles that govern the device performance, in particular, in the context of disclosing structure–property correlations.